Aqueous zinc ion battery electrolyte and preparation method and application thereof

By using electrolyte with zinc sulfate and cycloketone small molecule additives in aqueous zinc ion batteries, the problem of uneven electric field and hydrogen evolution reaction on the surface of zinc negative electrode is solved, and the stability and cycle life of zinc ion batteries are significantly improved, achieving high Performance battery applications.

CN119297436APending Publication Date: 2025-01-10CHONGQING TECH & BUSINESS UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411431783.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Under the working conditions of high current density and high area ratio, the uneven electric field distribution of the zinc negative electrode surface leads to uneven nucleation of zinc ions and the growth of zinc dendrites, which seriously affects the cycle life, and there are problems of hydrogen evolution reaction and zinc corrosion. It hinders its practical application.

Method used

The electrolyte is prepared by zinc sulfate and cycloketone small molecule additives (such as cyclohexanone, 1,2-cyclohexanedione, 1,3-cyclohexanedione, etc.), and mix it until it is completely dissolved by ultrasonic to form electrolysis at different concentrations. The liquid used to inhibit the growth and hydrogen evolution reaction of zinc dendrites, and explore the mechanism of the number and position of zinc-philic functional groups to the stability of zinc negative electrodes.

Benefits of technology

Effectively inhibit the growth of zinc dendrites and hydrogen evolution reaction, alleviate zinc corrosion, improve the stability and cycle life of zinc negative electrodes, and achieve high-performance and long-cycle stability of aqueous zinc ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297436A_ABST
    Figure CN119297436A_ABST
Patent Text Reader

Abstract

The invention discloses an aqueous zinc ion battery electrolyte as well as a preparation method and application thereof, and relates to the technical field of electrolytes. The electrolyte is modified by adding the cyclic ketone small-molecule additive into zinc sulfate, growth of zinc dendrites on the surface of the zinc negative electrode and hydrogen evolution reaction can be effectively inhibited, so that the problems of zinc corrosion and zinc negative electrode passivation are relieved, the mechanism of improving the stability of the zinc negative electrode by the quantity and position of zinc-philic functional group carbonyl is discussed, and the stability of the zinc negative electrode is improved. Experiments prove that the zinc ion battery prepared from the electrolyte successfully constructs the aqueous zinc ion battery with high performance and long cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrolytes, and in particular to an aqueous zinc ion battery electrolyte and a preparation method and application thereof. Background Art

[0002] The development and utilization of new energy sources promote the transformation of the energy industry towards a green and low-carbon direction. Green renewable energy sources such as solar energy, wind energy and tidal energy, as the main force of new energy, will play an important leading role. The development of energy storage devices with high energy density, safe and reliable use process, low manufacturing cost and simple recycling process is an important technical guarantee for solving the intermittent shortcomings of new energy and promoting the vigorous development of green energy economy. Due to its high specific energy density and mature preparation process technology, lithium-ion batteries (LIBs) are widely used in portable electronic devices and electric vehicles. However, the organic electrolyte used in commercial lithium batteries has certain safety hazards and high difficulty in subsequent recycling. The battery assembly needs to be carried out under harsh conditions, resulting in high manufacturing process costs, and the limited lithium resources on the earth make lithium-containing materials expensive. These problems have hindered the further development of lithium-ion batteries in the field of large-scale energy storage in the future to a certain extent. In contrast, water-based electrolyte secondary batteries have the characteristics of high flame retardancy and safety, simple and low-cost manufacturing process, high electrolyte ion conductivity and good environmental compatibility. Therefore, it is particularly important to develop water-based electrolyte chemical energy storage battery devices.

[0003] In the development and research of water-based electrolyte multivalent metal ion batteries, zinc ion secondary batteries are widely used because of their abundant raw material reserves, low price, low potential, and high theoretical capacity (820 mAh g -1 ), environmental friendliness and high safety have attracted wide attention. However, the uneven electric field distribution on the surface of the zinc negative electrode leads to uneven nucleation of zinc ions and growth of zinc dendrites. Especially at high current density (5mA·cm -2 ) and high area specific capacitance (50mAh·cm -2 ) working conditions, the side reactions (hydrogen evolution reaction and zinc corrosion) at the interface between the zinc electrode and the electrolyte intensify, which seriously affects the cycle life of the zinc electrode and hinders the practical application of aqueous zinc-ion batteries.

[0004] Therefore, effective measures are urgently needed to solve these problems faced by the negative electrode of aqueous zinc-ion batteries. So far, researchers have proposed many solutions, including artificial SEI membrane, negative electrode structure design, electrolyte solution modification, etc. Although there are many methods, the ideas are not the same. Among them, the additive-modified electrolyte strategy is a low-cost, simple and effective, and large-scale scalable zinc negative electrode protection strategy. In recent years, various inorganic and organic additives have been widely reported to be used to regulate Zn 2+The solvation structure of the additive can inhibit side reactions and control the nucleation-deposition process, thereby improving the electrochemical performance of aqueous zinc-ion batteries. However, there are few reports on the mechanism of improving the stability of zinc anodes by the number and position of zinc-philic functional groups in additives.

[0005] Therefore, a new solution to the above problems needs to be proposed. Summary of the invention

[0006] The object of the present invention is to provide an aqueous zinc ion battery electrolyte and a preparation method and application thereof, so as to solve the technical problems raised in the background technology.

[0007] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: an aqueous zinc ion battery electrolyte, comprising zinc sulfate, a solvent and a cyclic ketone small molecule additive, wherein the cyclic ketone small molecule additive comprises cyclohexanone, 1,2-cyclohexanedione, 1,3-cyclohexanedione, 1,4-cyclohexanedione, 1,3,5-cyclohexanetrione and cyclohexanone.

[0008] Furthermore, the cyclohexanone, 1,2-cyclohexanedione, 1,3-cyclohexanedione, 1,4-cyclohexanedione, 1,3,5-cyclohexanetrione and cyclohexanone respectively form independent electrolytes with the solvent.

[0009] Furthermore, the concentration of the zinc sulfate is 1-2 mol / L, and the concentration of the cyclic ketone small molecule additive is 0.5-4 mg / mL.

[0010] Preferably, the concentration of zinc sulfate is 2 mol / L, and the concentration of the cyclic ketone small molecule additive is 1 mg / mL.

[0011] Furthermore, the solvent includes at least water.

[0012] A method for preparing an aqueous zinc ion battery electrolyte, used for the above-mentioned aqueous zinc ion battery electrolyte, at least comprises the following steps:

[0013] A zinc sulfate solution of a certain concentration is prepared by using a solvent and zinc sulfate;

[0014] Add the cyclic ketone small molecule additive to the zinc sulfate solution and mix until it is completely dissolved;

[0015] Different aqueous zinc ion battery electrolytes are formed by adding different masses of cyclic ketone small molecule additives.

[0016] Further, at least the following steps are included:

[0017] S1: Weigh 14.378 g of zinc sulfate hexahydrate and use a 25 mL volumetric flask to make up to 2 mol / L blank ZnSO4 electrolyte;

[0018] S2: Take 12.5 mg of cyclohexanone and add it to the blank electrolyte prepared in S1, mix and ultrasonicate until the cyclohexanone is completely dissolved, and prepare a ZnSO4-0.5 mg / mL cyclohexanone electrolyte with a concentration of 2 mol / L;

[0019] S3: Take 12.5 mg 1,2-cyclohexanedione and add it to the blank electrolyte prepared in S1, mix and ultrasonicate until 1,2-cyclohexanedione is completely dissolved, and prepare a ZnSO4-0.5 mg / mL 1,2-cyclohexanedione electrolyte with a concentration of 2 mol / L;

[0020] S4: Take 25 mg of 1,2-cyclohexanedione and add it to the blank electrolyte prepared in S1, mix and sonicate until 1,2-cyclohexanedione is completely dissolved, and prepare a ZnSO4-1 mg / mL electrolyte with a concentration of 2 mol / L;

[0021] S5: Take 50 mg of 1,2-cyclohexanedione and add it to the blank electrolyte prepared in S1, mix and sonicate until 1,2-cyclohexanedione is completely dissolved, and prepare a ZnSO4-2 mg / mL electrolyte with a concentration of 2 mol / L;

[0022] S6: Take 100 mg of 1,2-cyclohexanedione and add it to the blank electrolyte prepared in S1, mix and sonicate until 1,2-cyclohexanedione is completely dissolved, and prepare a ZnSO4-4 mg / mL electrolyte with a concentration of 2 mol / L;

[0023] S7: Take 12.5 mg of 1,3-cyclohexanedione and add it to the blank electrolyte prepared in S1, mix and ultrasonicate until 1,3-cyclohexanedione is completely dissolved, and prepare a ZnSO4-0.5 mg / mL electrolyte with a concentration of 2 mol / L;

[0024] S8: Take 12.5 mg of 1,4-cyclohexanedione and add it to the blank electrolyte prepared in S1, mix and sonicate until 1,4-cyclohexanedione is completely dissolved, and prepare a ZnSO4-0.5 mg / mL electrolyte with a concentration of 2 mol / L;

[0025] S9: Take 12.5 mg of 1,3,5-cyclohexanetrione and add it to the blank electrolyte prepared in S1, mix and sonicate until 1,3,5-cyclohexanetrione is completely dissolved, and prepare a ZnSO4-0.5 mg / mL electrolyte with a concentration of 2 mol / L;

[0026] S10: Take 12.5 mg of cyclohexanone and add it to the blank electrolyte prepared in S1, mix and ultrasonicate until the cyclohexanone is completely dissolved, and prepare a ZnSO4-0.5 mg / mL electrolyte with a concentration of 2 mol / L.

[0027] An application of an aqueous zinc ion battery electrolyte, using the aqueous zinc ion battery electrolyte to prepare a zinc ion battery.

[0028] Furthermore, the zinc ion battery comprises, from bottom to top, a negative electrode shell, a negative electrode zinc sheet, a diaphragm, a positive electrode zinc sheet, a gasket, a spring and a positive electrode shell, and an aqueous zinc ion battery electrolyte is dripped onto the diaphragm.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention modifies the electrolyte by adding a cyclic ketone small molecule additive, which can effectively inhibit zinc dendrite growth and hydrogen evolution reaction on the surface of the zinc negative electrode, thereby alleviating the zinc corrosion and passivation problems of the zinc negative electrode.

[0031] The mechanism of the effect of the number and position of the carbonyl groups of the zinc-philic functional group on improving the stability of the zinc negative electrode was explored, and experiments proved that the zinc ion battery prepared by the electrolyte of the present invention successfully constructed a high-performance, long-cycle stability aqueous zinc ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0033] Figure 1 (a) is a graph showing the cycle performance test results of the Zn||Zn symmetrical batteries of Examples 1, 7, 8, and 9;

[0034] Figure 1 (b) is a graph showing the cycle performance test results of the Zn||Zn symmetrical batteries of Examples 1, 6, and 7;

[0035] Figure 2 (a) is the ionic conductivity diagram of stainless steel||stainless steel symmetric battery of Examples 10, 16, 17, and 18;

[0036] Figure 2 (b) is the ionic conductivity diagram of stainless steel||stainless steel symmetric battery of Examples 11, 15, and 16;

[0037] Figure 3 (a) is the AC impedance diagram of the Zn||Zn symmetrical battery of Examples 1, 7, 8, and 9;

[0038] Figure 3 (b) is the AC impedance diagram of the Zn||Zn symmetrical battery of Examples 1, 6, and 7;

[0039] Figure 4 (a) is a hydrogen evolution curve of the Zn||Zn symmetric battery of Examples 1, 7, 8, and 9;

[0040] Figure 4 (b) is a hydrogen evolution curve of the Zn||Zn symmetric battery of Examples 1, 6, and 7;

[0041] Figure 5 Graph showing the cycle performance test results of the Zn||Zn symmetrical batteries of Comparative Example 1 and Examples 2 to 5;

[0042] Figure 6 It is the ionic conductivity diagram of stainless steel||stainless steel symmetric battery of comparative example 2 and examples 11 to 14;

[0043] Figure 7 The AC impedance diagram of the Zn||Zn symmetrical battery of Comparative Example 1 and Examples 2 to 5;

[0044] Figure 8 It is a hydrogen evolution curve diagram of the Zn||Zn symmetric battery of comparative example 1 and embodiments 2 to 5;

[0045] Fig. 9 Graph showing the cycling performance test results of the Zn||Zn symmetrical battery of Comparative Example 1 and Example 3 at different rates;

[0046] Fig.10 The full batteries of Comparative Example 3 and Example 19 were subjected to CV testing;

[0047] Fig.11 Full battery long cycle performance test of Comparative Example 3 and Example 19;

[0048] Fig.12 Full cell rate performance diagram of Comparative Example 3 and Example 19;

[0049] Fig.13 XRD patterns of Zn||Zn symmetric batteries of Comparative Example 3 and Example 3 after cycling;

[0050] Fig.14 Characterization diagram of the Zn||Zn symmetric battery after deposition of Comparative Example 3 and Example 3. DETAILED DESCRIPTION

[0051] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0052] The present invention provides six zinc ion battery electrolyte combinations, containing zinc sulfate and cyclohexanone / 1,2-cyclohexanedione / 1,3-cyclohexanedione / 1,4-cyclohexanedione / 1,3,5-cyclohexanetrione / cyclohexanehexaone. The present invention has been experimentally verified to confirm that the electrolyte with the addition of cycloketone small molecule additives can effectively improve the various performances of zinc ion batteries.

[0053] Furthermore, the present invention provides a zinc ion battery electrolyte based on the above electrolyte composition, comprising the above composition and a solvent.

[0054] In the electrolyte, the final concentration of zinc sulfate is 2 mol / L, and the final concentration of the cyclic ketone small molecule additive is 0.5-4 mg / mL. The electrolyte prepared within this concentration range is used to assemble a zinc ion battery, which can effectively inhibit the growth of zinc dendrites and hydrogen evolution reaction on the surface of the zinc negative electrode, thereby alleviating the zinc corrosion and passivation problems of the zinc negative electrode.

[0055] For example: in the electrolyte, the final concentration of zinc sulfate is 1 mol / L, and the final concentration of cyclic ketone small molecules is 0.5 mg / mL. Or the final concentration of zinc sulfate is 1 mol / L, and the final concentration of cyclic ketone small molecules is 1 mg / mL. Or the final concentration of zinc sulfate is 1 mol / L, and the final concentration of cyclic ketone small molecules is 2 mg / mL. Or the final concentration of zinc sulfate is 1 mol / L, and the final concentration of cyclic ketone small molecules is 4 mg / mL.

[0056] In the above combination, preferably, the final concentration of zinc sulfate is 2 mol / L, and the final concentration of the cyclic ketone small molecule is 1 mg / mL.

[0057] The preparation method of the zinc ion battery electrolyte comprises the following steps: preparing a zinc sulfate solution of a certain concentration by using a solvent; adding cyclic ketone small molecules and mixing until the solution is completely dissolved.

[0058] The electrolytes involved in the following examples were prepared as follows:

[0059] (1) Weigh 14.378 g of zinc sulfate hexahydrate and dilute to volume in a 25 mL volumetric flask to prepare a blank ZnSO4 electrolyte with a concentration of 2 mol / L.

[0060] (2) 12.5 mg of cyclohexanone was added to the blank electrolyte prepared in step (1), and the mixture was mixed and ultrasonicated until the cyclohexanone was completely dissolved, thereby preparing a ZnSO4-0.5 mg / mL cyclohexanone electrolyte with a concentration of 2 mol / L.

[0061] (3) 12.5 mg of 1,2-cyclohexanedione was added to the blank electrolyte prepared in step (1), and the mixture was mixed and ultrasonicated until the 1,2-cyclohexanedione was completely dissolved to prepare a ZnSO4-0.5 mg / mL electrolyte with a concentration of 2 mol / L.

[0062] (4) Take 25 mg of 1,2-cyclohexanedione and add it to the blank electrolyte prepared in step (1), mix and ultrasonicate until 1,2-cyclohexanedione is completely dissolved, and prepare a ZnSO4-1 mg / mL electrolyte with a concentration of 2 mol / L.

[0063] (5) Take 50 mg of 1,2-cyclohexanedione and add it to the blank electrolyte prepared in step (1), mix and ultrasonicate until 1,2-cyclohexanedione is completely dissolved, and prepare a ZnSO4-2 mg / mL electrolyte with a concentration of 2 mol / L.

[0064] (6) Take 100 mg of 1,2-cyclohexanedione and add it to the blank electrolyte prepared in step (1), mix and sonicate until 1,2-cyclohexanedione is completely dissolved, and prepare a ZnSO4-4 mg / mL electrolyte with a concentration of 2 mol / L.

[0065] (7) Take 12.5 mg of 1,3-cyclohexanedione and add it to the blank electrolyte prepared in step (1), mix and ultrasonicate until 1,3-cyclohexanedione is completely dissolved, and prepare a ZnSO4-0.5 mg / mL electrolyte with a concentration of 2 mol / L.

[0066] (8) 12.5 mg of 1,4-cyclohexanedione was added to the blank electrolyte prepared in step (1), and the mixture was mixed and ultrasonicated until the 1,4-cyclohexanedione was completely dissolved to prepare a ZnSO4-0.5 mg / mL electrolyte with a concentration of 2 mol / L.

[0067] (9) 12.5 mg of 1,3,5-cyclohexanetrione was added to the blank electrolyte prepared in step (1), and the mixture was mixed and ultrasonicated until the 1,3,5-cyclohexanetrione was completely dissolved to prepare a ZnSO4-0.5 mg / mL electrolyte with a concentration of 2 mol / L.

[0068] (10) 12.5 mg of cyclohexanone was added to the blank electrolyte prepared in step (1), and the mixture was mixed and ultrasonicated until the cyclohexanone was completely dissolved, thereby obtaining a ZnSO4-0.5 mg / mL electrolyte with a concentration of 2 mol / L.

[0069] In addition, in the description of the present invention, it should be noted that, if no specific conditions are specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be purchased commercially.

[0070] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, which are intended to explain the present invention rather than to limit it.

[0071] Embodiment 1:

[0072] Zn||Zn symmetric battery with 2mol / L ZnSO4-0.5mg / mL cyclohexanone as electrolyte

[0073] Weigh 14.378 g of zinc sulfate hexahydrate and 12.5 mg of cyclohexanone, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to completely dissolve it to prepare a 2 mol / L ZnSO4-0.5 mg / mL cyclohexanone electrolyte.

[0074] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially placed. When assembling the diaphragm, 100uL (2mol / LZnSO4-0.5mg / mL cyclohexanone) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.

[0075] Embodiment 2:

[0076] Zn||Zn symmetric battery with 2mol / L ZnSO4-0.5mg / mL 1,2-cyclohexanedione as electrolyte

[0077] Weigh 14.378 g of zinc sulfate hexahydrate and 12.5 mg of 1,2-cyclohexanedione, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to make it completely dissolved to prepare an electrolyte with a concentration of 2 mol / L ZnSO4-0.5 mg / mL 1,2-cyclohexanedione.

[0078] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially installed. When installing the diaphragm, 100uL (2mol / LZnSO4-0.5mg / mL1,2-cyclohexanedione) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.

[0079] Embodiment 3:

[0080] Zn||Zn symmetric battery with 2 mol / L ZnSO4-1 mg / mL 1,2-cyclohexanedione as electrolyte

[0081] Weigh 14.378 g of zinc sulfate hexahydrate and 25 mg of 1,2-cyclohexanedione, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to make it completely dissolved to prepare an electrolyte with a concentration of 2 mol / LZnSO4-1 mg / mL1,2-cyclohexanedione.

[0082] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially placed. When assembling the diaphragm, 100uL (2mol / LZnSO4-1mg / mL1,2-cyclohexanedione) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.

[0083] Embodiment 4:

[0084] Zn||Zn symmetric battery with 2 mol / L ZnSO4-2 mg / mL 1,2-cyclohexanedione as electrolyte

[0085] Weigh 14.378 g of zinc sulfate hexahydrate and 50 mg of 1,2-cyclohexanedione, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to completely dissolve it to prepare an electrolyte with a concentration of 2 mol / LZnSO4-2 mg / mL1,2-cyclohexanedione.

[0086] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially placed. When assembling the diaphragm, 100uL (2mol / LZnSO4-2mg / mL1,2-cyclohexanedione) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.

[0087] Embodiment 5:

[0088] Zn||Zn symmetric battery with 2 mol / L ZnSO4-4 mg / mL 1,2-cyclohexanedione as electrolyte

[0089] Weigh 14.378 g of zinc sulfate hexahydrate and 100 mg of 1,2-cyclohexanedione, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner for ultrasonic cleaning to completely dissolve it to prepare an electrolyte with a concentration of 2 mol / LZnSO4-4 mg / mL1,2-cyclohexanedione.

[0090] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially placed. When assembling the diaphragm, 100uL (2mol / LZnSO4-4mg / mL1,2-cyclohexanedione) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.

[0091] Embodiment 6:

[0092] A Zn||Zn symmetric battery with 2 mol / L ZnSO4-0.5 mg / mL 1,3-cyclohexanedione as electrolyte

[0093] Weigh 14.378 g of zinc sulfate hexahydrate and 12.5 mg of 1,3-cyclohexanedione, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to completely dissolve it to prepare an electrolyte with a concentration of 2 mol / L ZnSO4-0.5 mg / mL 1,3-cyclohexanedione.

[0094] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially placed. When installing the diaphragm, 100uL (2mol / LZnSO4-0.5mg / mL1,3-cyclohexanedione) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.

[0095] Embodiment 7:

[0096] A Zn||Zn symmetric battery with 2 mol / L ZnSO4-0.5 mg / mL 1,4-cyclohexanedione as electrolyte

[0097] Weigh 14.378 g of zinc sulfate hexahydrate and 12.5 mg of 1,4-cyclohexanedione, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to completely dissolve it to prepare an electrolyte with a concentration of 2 mol / L ZnSO4-0.5 mg / mL 1,4-cyclohexanedione.

[0098] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially placed. When installing the diaphragm, 100uL (2mol / LZnSO4-0.5mg / mL1,4-cyclohexanedione) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.

[0099] Embodiment 8:

[0100] A Zn||Zn symmetric battery with 2 mol / L ZnSO4-0.5 mg / mL 1,3,5-cyclohexanetrione as electrolyte

[0101] Weigh 14.378 g of zinc sulfate hexahydrate and 12.5 mg of 1,3,5-cyclohexanetrione, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to make it completely dissolved to prepare an electrolyte with a concentration of 2 mol / LZnSO4-0.5 mg / mL1,3,5-cyclohexanetrione.

[0102] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially placed. When installing the diaphragm, 100uL (2mol / LZnSO4-0.5mg / mL1,3,5-cyclohexanetrione) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.

[0103] Embodiment 9:

[0104] Zn||Zn symmetric battery with 2mol / L ZnSO4-0.5mg / mL cyclohexanehexone as electrolyte

[0105] Weigh 14.378 g of zinc sulfate hexahydrate and 12.5 mg of cyclohexanone, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to make it completely dissolved to prepare a 2 mol / L ZnSO4-0.5 mg / mL cyclohexanone electrolyte.

[0106] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially placed. When assembling the diaphragm, 100uL (2mol / LZnSO4-0.5mg / mL cyclohexanehexaketone) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.

[0107] Embodiment 10:

[0108] Stainless steel || Stainless steel symmetric battery with 2mol / L ZnSO4-0.5mg / mL cyclohexanone as electrolyte

[0109] Weigh 14.378 g of zinc sulfate hexahydrate and 12.5 mg of cyclohexanone, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to completely dissolve it to prepare a 2 mol / L ZnSO4-0.5 mg / mL cyclohexanone electrolyte.

[0110] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, 16mm diameter stainless steel (as the negative electrode), 16mm diameter diaphragm (Glass microfiber lilters), 12mm diameter stainless steel (as the positive electrode), gasket, spring, and positive electrode shell are sequentially installed. When installing the diaphragm, 100uL (2mol / LZnSO4-0.5mg / mL cyclohexanone) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a stainless steel||stainless steel symmetrical battery.

[0111] Embodiment 11:

[0112] Stainless steel || Stainless steel symmetric cell with 2 mol / L ZnSO4-0.5 mg / mL 1,2-cyclohexanedione as electrolyte

[0113] Weigh 14.378 g of zinc sulfate hexahydrate and 12.5 mg of 1,2-cyclohexanedione, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to make it completely dissolved to prepare an electrolyte with a concentration of 2 mol / L ZnSO4-0.5 mg / mL 1,2-cyclohexanedione.

[0114] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, 16mm diameter stainless steel (as the negative electrode), 16mm diameter diaphragm (Glass microfiber lilters), 12mm diameter stainless steel (as the positive electrode), gasket, spring, and positive electrode shell are sequentially installed. When installing the diaphragm, 100uL (2mol / LZnSO4-0.5mg / mL1,2-cyclohexanedione) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a stainless steel||stainless steel symmetrical battery.

[0115] Embodiment 12:

[0116] Stainless steel with 2 mol / L ZnSO4-1 mg / mL 1,2-cyclohexanedione as electrolyte || Stainless steel symmetric cell

[0117] Weigh 14.378 g of zinc sulfate hexahydrate and 25 mg of 1,2-cyclohexanedione, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to make it completely dissolved to prepare an electrolyte with a concentration of 2 mol / LZnSO4-1 mg / mL1,2-cyclohexanedione.

[0118] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, 16mm diameter stainless steel (as the negative electrode), 16mm diameter diaphragm (Glass microfiber lilters), 12mm diameter stainless steel (as the positive electrode), gasket, shrapnel, and positive electrode shell are placed in sequence. When installing the diaphragm, 100uL (2mol / LZnSO4-1 mg / mL1,2-cyclohexanedione) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a stainless steel||stainless steel symmetrical battery.

[0119] Embodiment 13:

[0120] Stainless steel with 2 mol / L ZnSO4-2 mg / mL 1,2-cyclohexanedione as electrolyte || Stainless steel symmetric cell

[0121] Weigh 14.378 g of zinc sulfate hexahydrate and 50 mg of 1,2-cyclohexanedione, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to completely dissolve it to prepare an electrolyte with a concentration of 2 mol / LZnSO4-2 mg / mL1,2-cyclohexanedione.

[0122] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, stainless steel with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), stainless steel with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially installed. When installing the diaphragm, 100uL (2mol / LZnSO4-2 mg / mL1,2-cyclohexanedione) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a stainless steel||stainless steel symmetrical battery.

[0123] Embodiment 14:

[0124] Stainless steel with 2 mol / L ZnSO4-4 mg / mL 1,2-cyclohexanedione as electrolyte || Stainless steel symmetric cell

[0125] Weigh 14.378 g of zinc sulfate hexahydrate and 100 mg of 1,2-cyclohexanedione, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner for ultrasonic cleaning to completely dissolve it to prepare an electrolyte with a concentration of 2 mol / LZnSO4-4 mg / mL1,2-cyclohexanedione.

[0126] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, stainless steel with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), stainless steel with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially installed. When installing the diaphragm, 100uL (2mol / LZnSO4-4 mg / mL1,2-cyclohexanedione) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a stainless steel||stainless steel symmetrical battery.

[0127] Embodiment 15:

[0128] Stainless steel with 2 mol / L ZnSO4-0.5 mg / mL 1,3-cyclohexanedione as electrolyte || Stainless steel symmetric cell

[0129] Weigh 14.378 g of zinc sulfate hexahydrate and 12.5 mg of 1,3-cyclohexanedione, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to completely dissolve it to prepare an electrolyte with a concentration of 2 mol / L ZnSO4-0.5 mg / mL 1,3-cyclohexanedione.

[0130] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, 16mm diameter stainless steel (as the negative electrode), 16mm diameter diaphragm (Glass microfiber lilters), 12mm diameter stainless steel (as the positive electrode), gasket, spring, and positive electrode shell are sequentially installed. When installing the diaphragm, 100uL (2mol / LZnSO4-0.5mg / mL1,3-cyclohexanedione) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a stainless steel||stainless steel symmetrical battery.

[0131] Embodiment 16:

[0132] Stainless steel with 2 mol / L ZnSO4-0.5 mg / mL 1,4-cyclohexanedione as electrolyte || Stainless steel symmetric cell

[0133] Weigh 14.378 g of zinc sulfate hexahydrate and 12.5 mg of 1,4-cyclohexanedione, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to completely dissolve it to prepare an electrolyte with a concentration of 2 mol / L ZnSO4-0.5 mg / mL 1,4-cyclohexanedione.

[0134] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, 16mm diameter stainless steel (as the negative electrode), 16mm diameter diaphragm (Glass microfiber lilters), 12mm diameter stainless steel (as the positive electrode), gasket, spring, and positive electrode shell are sequentially installed. When installing the diaphragm, 100uL (2mol / LZnSO4-0.5mg / mL1,4-cyclohexanedione) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a stainless steel||stainless steel symmetrical battery.

[0135] Embodiment 17:

[0136] Stainless steel with 2mol / L ZnSO4-0.5mg / mL 1,3,5-cyclohexanetrione as electrolyte || Stainless steel symmetric cell

[0137] Weigh 14.378 g of zinc sulfate hexahydrate and 12.5 mg of 1,3,5-cyclohexanetrione, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to make it completely dissolved to prepare an electrolyte with a concentration of 2 mol / LZnSO4-0.5 mg / mL1,3,5-cyclohexanetrione.

[0138] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, stainless steel with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), stainless steel with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially installed. When installing the diaphragm, 100uL (2mol / LZnSO4-0.5mg / mL1,3,5-cyclohexanetrione) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a stainless steel||stainless steel symmetrical battery.

[0139] Embodiment 18:

[0140] Stainless steel || Stainless steel symmetric battery with 2mol / L ZnSO4-0.5mg / mL cyclohexanehexone as electrolyte

[0141] Weigh 14.378 g of zinc sulfate hexahydrate and 12.5 mg of cyclohexanone, and use a 25 mL volumetric flask to make up the volume. Place it in a CNC ultrasonic cleaner and ultrasonicate it to make it completely dissolved to prepare a 2 mol / L ZnSO4-0.5 mg / mL cyclohexanone electrolyte.

[0142] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, stainless steel with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), stainless steel with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially installed. When installing the diaphragm, 100uL (2mol / LZnSO4-0.5mg / mL cyclohexanehexone (electrolyte) is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a stainless steel||stainless steel symmetrical battery.

[0143] Embodiment 19:

[0144] Zinc-manganese dioxide full battery with 2 mol / L ZnSO4-1 mg / mL 1,2-cyclohexanedione as electrolyte

[0145] Manganese dioxide, conductive carbon black, and PVDF were mixed in a mass ratio of 7:2:1 and stirred for 12 hours to prepare a uniform electrode slurry, which was then coated on a stainless steel foil with a coating thickness of 15 μm. After condensation and drying for 24 hours, a positive electrode sheet was obtained. A solution of 2 mol / L ZnSO4-1 mg / mL 1,2-cyclohexanedione was then used as the electrolyte.

[0146] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the positive electrode sheet for preparing the positive electrode material, the gasket, the spring, and the positive electrode shell are placed in sequence. When installing the diaphragm, 100uL of electrolyte (2mol / LZnSO4-1 mg mL1,2-cyclohexanedione) is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a zinc-manganese dioxide full battery.

[0147] Comparative Example 1:

[0148] Zn||Zn symmetric battery with 2 mol / L ZnSO4 as electrolyte

[0149] Weigh 14.378 g of zinc sulfate hexahydrate, and use a 25 mL volumetric flask to make up the volume. Place it in a numerically controlled ultrasonic cleaner for ultrasonic cleaning to completely dissolve it, and prepare a blank ZnSO4 electrolyte with a concentration of 2 mol / L.

[0150] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the zinc sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially placed. When assembling the diaphragm, 100uL (2mol / LZnSO4) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a Zn||Zn symmetrical battery.

[0151] Comparative Example 2:

[0152] Stainless steel with 2 mol / L ZnSO4 as electrolyte || Stainless steel symmetrical battery

[0153] Weigh 14.378 g of zinc sulfate hexahydrate, and use a 25 mL volumetric flask to make up the volume. Place it in a numerically controlled ultrasonic cleaner for ultrasonic cleaning to completely dissolve it, and prepare a blank ZnSO4 electrolyte with a concentration of 2 mol / L.

[0154] In the button CR2032 battery mold, from bottom to top, the negative electrode shell, the stainless steel sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the stainless steel sheet with a diameter of 12mm (as the positive electrode), the gasket, the spring, and the positive electrode shell are sequentially placed. When assembling the diaphragm, 100uL (2mol / LZnSO4) electrolyte is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a stainless steel||stainless steel symmetrical battery.

[0155] Comparative Example 3:

[0156] Zinc-manganese dioxide full battery with 2 mol / L ZnSO4 as electrolyte

[0157] Manganese dioxide, conductive carbon black and PVDF were mixed in a mass ratio of 7:2:1 and stirred for 12 hours to prepare a uniform electrode slurry, which was then coated on a stainless steel foil and condensed and dried for 24 hours to obtain a positive electrode sheet. A solution with a concentration of 2 mol / L ZnSO4 was then used as the electrolyte.

[0158] In the button CR2032 battery mold, the negative electrode shell, the zinc sheet with a diameter of 16mm (as the negative electrode), the diaphragm with a diameter of 16mm (Glass microfiber lilters), the positive electrode sheet for preparing the positive electrode material, the gasket, the spring, and the positive electrode shell are placed from bottom to top. When assembling the diaphragm, 100uL of electrolyte (2mol / LZnSO4) is dripped onto the diaphragm. After the assembly is completed, the button battery is finally sealed with a tablet press to assemble a zinc-manganese dioxide full battery.

[0159] Performance test of the above case:

[0160] Experiment 1: (a) Comparison of the cycling performance of the Zn||Zn symmetric batteries of Examples 1, 7, 8, and 9; (b) Comparison of the cycling performance of the Zn||Zn symmetric batteries of Examples 1, 6, and 7.

[0161] The five Zn||Zn symmetric batteries obtained above were charged and discharged in the blue dot cycle system at a current of 1.0 mA cm -2 , with a fixed charge and discharge capacity of 1 mAh cm -2 The cycle performance test was carried out under the conditions of Figure 1 As shown in (a), in the cycle comparison test of different amounts of cycloketone small molecules, 1,3,5-cyclohexanetrione showed better cycle performance. The reason is that a small amount of carbonyl functional groups cannot provide enough active sites and cannot fully inhibit the activity of water, while excessive carbonyl functional groups will produce strong steric hindrance, thereby enhancing the shielding effect on the Zn negative electrode and causing a higher energy barrier for Zn deposition. Figure 1 (b) 1,2-cyclohexanedione exhibits better cycle performance. The main reason is that the ortho carbonyl group can fully contact with the Zn surface and can be fully utilized under the same active site. It can also better inhibit the activity of water under the same steric hindrance, so the performance is more stable.

[0162] Experiment 2: (a) Testing of ionic conductivity of stainless steel||stainless steel symmetric battery in Examples 10, 16, 17, and 18; (b) Testing of ionic conductivity of stainless steel||stainless steel symmetric battery in Examples 11, 15, and 16

[0163] The ionic conductivity of the five stainless steel||stainless steel symmetrical cells in the experimental group obtained above was tested in the electrochemical workstation chi660e with the low frequency set to 0.01 Hz, the high frequency set to 100000 Hz, and the initial voltage set to 0.01 V.

[0164] The results are as follows Figure 2 As shown, cyclic ketone small molecules with different numbers of carbonyl groups and different positions were determined as electrolyte additives. 1,3,5-cyclohexanetrione and 1,2-cyclohexanedione showed better ionic conductivity, which was mainly due to the presence of hydrophilic groups. The cyclic ketone small molecules have higher hydrophilicity, thereby improving the electrolyte absorption capacity and ionic conductivity of the additive, achieving rapid charge transfer, and showing excellent electrochemical stability.

[0165] Experiment 3: (a) AC impedance performance test of Zn||Zn symmetrical batteries of Examples 1, 7, 8, and 9; (b) AC impedance performance test of Zn||Zn symmetrical batteries of Examples 1, 6, and 7

[0166] For the four Zn||Zn symmetrical batteries in the experimental group obtained above, the AC impedance was tested in the electrochemical workstation chi660e with the low frequency set to 0.01 Hz, the high frequency set to 100000 Hz and the initial voltage set to 0.01 V.

[0167] The results are as follows Figure 3 As shown, the result is exactly the same as Figure 2 Corresponding to the ionic conductivity, the smaller the AC impedance is, the better the conductivity of the battery is, and the longer the battery cycle time will be.

[0168] Experiment 4: (a) Hydrogen evolution curve test of Zn||Zn symmetric battery of Examples 1, 7, 8, and 9; (b) Hydrogen evolution curve test of Zn||Zn symmetric battery of Examples 1, 6, and 7

[0169] The four Zn||Zn symmetric batteries obtained above were tested for hydrogen evolution curves in an electrochemical workstation chi660e with an initial voltage of -0.5V and a final voltage of 0.5V.

[0170] The results are as follows Figure 4 As shown in the figure, the fitted corrosion current density of the Zn||Zn symmetric cell in 1,3,5-cyclohexanetrione electrolyte is 0.103 mA cm -2The fitted corrosion current density of the Zn symmetric cell of 1,2-cyclohexanedione is 0.0776 mA cm -2 , which are significantly lower than the corrosion current density of the same group. This structure shows that the electrolyte additive can effectively reduce the corrosion rate of the Zn negative electrode, thereby improving the stability of ZIB.

[0171] Experiment 5: Comparison of Cycling Performance of Zn||Zn Symmetric Batteries of Comparative Example 1 and Examples 2 to 5

[0172] The five Zn||Zn symmetric batteries obtained above were charged and discharged in a lithium battery cycle system at a charge and discharge current of 1.0 mA cm -2 , with a fixed charge and discharge capacity of 1 mAh cm -2 The cycle performance test was carried out under the conditions of

[0173] The results are as follows Figure 5 As shown in the figure, the long cycle stability performance of ZnSO4 and additives of different concentrations, it can be seen that the cycle of the electrolyte with additives is more than 1000 hours, among which the Zn||Zn symmetric battery containing 1mg / mL 1,2-cyclohexanedione electrolyte shows the best cycle stability, while the battery assembled with zinc sulfate has serious voltage hysteresis and dies after 200 hours. For other concentrations of electrolyte, the cycle performance of the battery is reduced, which may be because when the electrolyte concentration is insufficient, it cannot provide sufficient active sites to induce Zn 2+ Deposition of zinc, too high a concentration will lead to increased corrosion on the zinc surface.

[0174] Experiment 6: Test of ionic conductivity of stainless steel of comparative example 2 and examples 11 to 14 || stainless steel symmetric battery

[0175] The ionic conductivity of the five stainless steel||stainless steel symmetrical cells in the experimental group obtained above was tested in the electrochemical workstation chi660e with the low frequency set to 0.01 Hz, the high frequency set to 100000 Hz, and the initial voltage set to 0.01 V.

[0176] The results are as follows Figure 6 As shown in the figure, the ionic conductivity of the added 1,2-cyclohexanedione is higher than that of the blank zinc sulfate, indicating that 1,2-cyclohexanedione is beneficial to the charge transfer at the interface. And with the increase of the concentration of 1,2-cyclohexanedione electrolyte, the ionic conductivity will also increase, which can be attributed to the higher total ion concentration in the electrolyte.

[0177] Experiment 7: AC impedance performance test of Zn||Zn symmetrical batteries of comparative example 1 and examples 2 to 5

[0178] For the five Zn||Zn symmetrical batteries in the experimental group obtained above, the AC impedance was tested in the electrochemical workstation chi660e with the low frequency set to 0.01 Hz, the high frequency set to 100000 Hz and the initial voltage set to 0.01 V.

[0179] The results are as follows Figure 7 As shown in Figure 2, as the concentration of 1,2-cyclohexanedione electrolyte increases, its AC impedance decreases continuously, and the results are consistent with Figure 6 The ionic conductivity results correspond to the smaller AC impedance, indicating that the electrolyte can effectively improve the hydrated Zn 2+ This leads to faster Zn deposition kinetics.

[0180] Experiment 8: Hydrogen evolution curve test of Zn||Zn symmetric battery of comparative example 1 and examples 2 to 5

[0181] The five Zn||Zn symmetric batteries obtained above were tested for hydrogen evolution curves in an electrochemical workstation chi660e with an initial voltage of -0.5V and a final voltage of 0.5V.

[0182] The results are as follows Figure 8 As shown in the figure, with the increase of 1,2-cyclohexanedione concentration, its corrosion current density first decreases and then increases, indicating that its corrosion resistance first increases and then decreases. The reason is that the electrolyte after adding 1,2-cyclohexanedione can be evenly deposited on the Zn surface, preventing the corrosion of the zinc surface during the charge and discharge process. Then, because the additive itself is acidic, when the concentration continues to increase, it will also cause a certain degree of corrosion to the zinc surface. In addition, as the electrolyte concentration continues to increase, its impedance continues to decrease, which accelerates the ion transmission capacity, which in turn leads to an increase in corrosion current density. Finally, 1mgmL -1 The 1,2-cyclohexanedione is the most effective in inhibiting zinc corrosion.

[0183] Experiment 9: Comparison of the cycling performance of Zn||Zn symmetric batteries of Comparative Example 1 and Example 3 at different rates

[0184] The two Zn||Zn symmetrical batteries obtained above were placed in a blue electricity test system and the charge and discharge current was set to 1.0 mA cm -2 , with a fixed charge and discharge capacity of 1 mAh cm -2 The cycle performance test was carried out under the conditions with a charge and discharge current of 4.0 mA cm -2 , with a fixed charge and discharge capacity of 4 mAh cm -2 The cycle performance test was carried out under the conditions and the charge and discharge current was 8.0 mA cm -2 , with a fixed charge and discharge capacity of 1.0 mAh cm -2 The cycle performance test was carried out under the following conditions.

[0185] The results are as follows Fig. 9 As shown, regardless of the current density of the charge-discharge cycle, the concentration of 2 mol / L ZnSO4-1 mg mL -1 The cycling performance of the Zn||Zn symmetric battery in the 1,2-cyclohexanone electrolyte is significantly better than that of the blank 2mol / LZnSO4 electrolyte. In the absence of 1,2-cyclohexanedione additive, higher overpotentials were found at each current density stage, while lower overpotentials and stable voltages were shown in the electrolyte assisted by 1,2-cyclohexanedione. This indicates that the 1,2-cyclohexanedione additive accelerates the mobility of ions during the Zn deposition / stripping process, which is consistent with the lower AC impedance results mentioned above.

[0186] Experiment 10: CV test of the full battery of Example 3 and Example 19

[0187] In order to verify the practicality of the 1,2-cyclohexanedione system in the full battery of AZIB, the full battery was tested on the chi660e electrochemical workstation, and the test results are shown in Fig.10 The cyclic voltammogram of the full cell is shown below. ... -1 The CV curves of MnO2 based on ZSO and 1,2-cyclohexanedione showed similar peak shapes when scanned at a rate of 2.5 Å. This indicated that the electrochemical redox mechanism of MnO2 remained well maintained.

[0188] Experiment 11: Full battery long cycle performance test of comparative example 3 and embodiment 19

[0189] Fig.11 The long-term cycling stability of the full battery at 0.5Ag-1 is shown. The full battery with the addition of 1,2-cyclohexanedione electrolyte exhibits excellent cycling stability, and the battery capacity remains at 300mAh g after 100 cycles. -1 In contrast, the full battery with only ZSO electrolyte suffered from rapid and continuous capacity decay, with a capacity of less than 50 mAh g after 100 cycles. -1 , and its coulombic efficiency is only close to 90%. The above results show that the electrolyte additive improves the long-term cycle performance of the full battery and has better battery capacity retention and coulombic efficiency.

[0190] Experiment 12: Full-battery rate performance diagram of comparative example 3 and example 19

[0191] like Fig.12 It can be observed that when the current density increases from 0.2A -1 Increase to 2Ag -1The full cell with 1,2-cyclohexanedione electrolyte provides a more excellent rate performance, and when the current density returns to 0.2Ag -1 When the electrolyte additives are used, the full cell with the electrolyte additive achieves the highest capacity retention rate of 88.95%, while the ZSO has only a capacity retention rate of 43.42%.

[0192] Experiment 13: Characterization of Zn negative electrode before and after cycling of Zn||Zn symmetric battery of comparative example 3 and example 3

[0193] The Zn||Zn symmetric cells of Comparative Example 3 and Example 9 were subjected to XRD tests after 3 and 50 cycles. Fig.13 As shown, from the XRD characterization of the zinc negative electrode after only 3 cycles, it can be seen that no by-products are generated after adding 1,2-cyclohexanedione electrolyte, while a small amount of hydroxy zinc sulfate is generated in the electrolyte without the additive 1,2-cyclohexanedione. In the XRD characterization diagram after 50 cycles, the by-products in the electrolyte with 1,2-cyclohexanedione added are significantly less than those in the electrolyte without 1,2-cyclohexanedione. This shows that 1,2-cyclohexanedione can inhibit the formation of zinc dendrites. Then we also performed SEM tests on the deposited zinc foil, such as Fig.14 As shown, at 1 mAh cm -2 From the SEM images at the current density of 10 min, 30 min, and 60 min, it can be seen that the zinc anode deposited in the blank ZSO electrolyte has a large number of protruding zinc dendrites and an uneven surface. The electrolyte based on 1,2-cyclohexanedione shows a flat surface during deposition and almost no zinc dendrites are generated.

[0194] In summary, the zinc ion battery of the present invention has good stability and rate performance, is beneficial to inhibiting the growth of zinc dendrites and the generation of by-products, and has obvious improvements in electrochemical properties such as cycle performance and rate performance compared to traditional aqueous zinc ion batteries.

[0195] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An aqueous zinc ion battery electrolyte, characterized in that: The invention comprises zinc sulfate, a solvent and a cycloketone small molecule additive, wherein the cycloketone small molecule additive comprises cyclohexanone, 1,2-cyclohexanedione, 1,3-cyclohexanedione, 1,4-cyclohexanedione, 1,3,5-cyclohexanetrione and cyclohexanone.

2. An aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The cyclohexanone, 1,2-cyclohexanedione, 1,3-cyclohexanedione, 1,4-cyclohexanedione, 1,3,5-cyclohexanetrione and cyclohexanehexaone respectively form independent electrolytes with zinc sulfate and a solvent.

3. An aqueous zinc ion battery electrolyte according to claim 2, characterized in that: The concentration of the zinc sulfate is 1-2 mol / L, and the concentration of the cyclic ketone small molecule additive is 0.5-4 mg / mL.

4. An aqueous zinc ion battery electrolyte and its preparation method and application according to claim 3, characterized in that: The concentration of the zinc sulfate is 2 mol / L, and the concentration of the cyclic ketone small molecule additive is 1 mg / mL.

5. An aqueous zinc ion battery electrolyte according to claim 4, characterized in that: The solvent is water.

6. A method for preparing an aqueous zinc ion battery electrolyte, used for an aqueous zinc ion battery electrolyte according to any one of claims 1 to 5, characterized in that: At least the following steps are included: A zinc sulfate solution of a certain concentration is prepared by using a solvent and zinc sulfate; Add the cyclic ketone small molecule additive to the zinc sulfate solution and mix until it is completely dissolved; Different aqueous zinc ion battery electrolytes are formed by adding different masses of cyclic ketone small molecule additives.

7. A method for preparing an aqueous zinc ion battery electrolyte according to claim 6, characterized in that: At least the following steps are included: S1: Weigh 14.378 g of zinc sulfate hexahydrate and use a 25 mL volumetric flask to make up to 2 mol / L blank ZnSO4 electrolyte; S2: Take 12.5 mg of cyclohexanone and add it to the blank electrolyte prepared in S1, mix and ultrasonicate until the cyclohexanone is completely dissolved, and prepare a ZnSO4-0.5 mg / mL cyclohexanone electrolyte with a concentration of 2 mol / L; S3: Take 12.5 mg 1,2-cyclohexanedione and add it to the blank electrolyte prepared in S1, mix and ultrasonicate until 1,2-cyclohexanedione is completely dissolved, and prepare a ZnSO4-0.5 mg / mL 1,2-cyclohexanedione electrolyte with a concentration of 2 mol / L; S4: Take 25 mg of 1,2-cyclohexanedione and add it to the blank electrolyte prepared in S1, mix and sonicate until 1,2-cyclohexanedione is completely dissolved, and prepare a ZnSO4-1 mg / mL electrolyte with a concentration of 2 mol / L; S5: Take 50 mg of 1,2-cyclohexanedione and add it to the blank electrolyte prepared in S1, mix and sonicate until 1,2-cyclohexanedione is completely dissolved, and prepare a ZnSO4-2 mg / mL electrolyte with a concentration of 2 mol / L; S6: Take 100 mg of 1,2-cyclohexanedione and add it to the blank electrolyte prepared in S1, mix and sonicate until 1,2-cyclohexanedione is completely dissolved, and prepare a ZnSO4-4 mg / mL electrolyte with a concentration of 2 mol / L; S7: Take 12.5 mg of 1,3-cyclohexanedione and add it to the blank electrolyte prepared in S1, mix and ultrasonicate until 1,3-cyclohexanedione is completely dissolved, and prepare a ZnSO4-0.5 mg / mL electrolyte with a concentration of 2 mol / L; S8: Take 12.5 mg of 1,4-cyclohexanedione and add it to the blank electrolyte prepared in S1, mix and sonicate until 1,4-cyclohexanedione is completely dissolved, and prepare a ZnSO4-0.5 mg / mL electrolyte with a concentration of 2 mol / L; S9: Take 12.5 mg of 1,3,5-cyclohexanetrione and add it to the blank electrolyte prepared in S1, mix and sonicate until 1,3,5-cyclohexanetrione is completely dissolved, and prepare a ZnSO4-0.5 mg / mL electrolyte with a concentration of 2 mol / L; S10: Take 12.5 mg of cyclohexanone and add it to the blank electrolyte prepared in S1, mix and ultrasonicate until the cyclohexanone is completely dissolved, and prepare a ZnSO4-0.5 mg / mL electrolyte with a concentration of 2 mol / L.

8. An application of an aqueous zinc ion battery electrolyte, characterized in that: The aqueous zinc ion battery electrolyte according to any one of claims 1 to 5 is used to prepare a zinc ion battery.

9. The use of an aqueous zinc ion battery electrolyte according to claim 8, characterized in that: The zinc ion battery comprises, from bottom to top, a negative electrode shell, a negative electrode zinc sheet, a diaphragm, a positive electrode zinc sheet, a gasket, a spring and a positive electrode shell, and an aqueous zinc ion battery electrolyte is dripped onto the diaphragm.

Citation Information

Cited By

  • Electrolyte and zinc-based battery

    CN120933505A

  • Electrolyte and zinc-based battery

    CN120933505B